Expression pattern of p53-binding protein 1 as a new molecular indicator of genomic instability in bladder urothelial carcinoma. Issue 1 (December 2018) - Matsuda, Katsuya; Kawasaki, Tatsuhiko; Akazawa, Yuko; Hasegawa, Yuhmi; Kondo, Hisayoshi; Suzuki, Keiji; Iseki, Masachika; Nakashima, Masahiro
Abstract Copy number alterations and loss of heterozygosity are associated with increasing tumor grade and bladder cancer stage. Our previous study suggested that co-expression of Ki-67 and p53-binding protein 1 (53BP1) could provide an indicator of an abnormal DNA damage response (DDR) pathway. The present study investigated 53BP1 expression as a novel molecular marker in urothelial carcinoma (UC) using bladder tissues with in total of 40 cases including a normal urothelium, urothelial papilloma, low-grade UC, or high-grade UC. Double-label immunofluorescence was used to analyze 53BP1 and Ki-67 expression. This was compared with the level of chromosomal instability and with the expression of other DDR molecules catalytic subunit. This study identified clear differences in the 53BP1 expression patterns in urothelial carcinogenesis, and their close association with genomic instability. 53BP1 abnormal immunoreactivity, particularly with co-localization of Ki-67, was restricted to malignant tissues. Our analyses indicated that a cut-off of >4% of nuclei with 53BP1 abnormal expression plus Ki-67 immunoreactivity distinguished high-grade UC from low-grade UC with 80.0% sensitivity and 100% specificity. We therefore propose that double immunofluorescent analysis of 53BP1 and Ki-67 expression could provide a useful tool to estimate the chromosomal instability and malignant potential of urothelial tumors.